Literasi Media dan Interpretasi atas Bencana - Wisnu Martha Adiputra (Jurnal Ilmu Sosial dan Ilmu Politik, 2008)
One of the most important things facing the disaster is the media literacy of disaster information. This paper will examine the role of literacy of disaster information on disaster event. First, it will explore the theoretical concept of media literacy. Second, it will explore the role of communication technology and understanding of disaster message. Third, it will explore the interpretation skill toward disaster information. Socio-cultural contexts of societal environment are being important to produce the literacy skill toward disaster information.